Acute renal failure and severe thrombocytopenia in a young boy with vivax malaria - dayal, Devi; Jabbar, Zulfikar; Kumar, Selva; Singh, Meenu (Journal of Pediatric Infectious Diseases, 2008)
This 7-year-old boy presented with acute renal failure associated with Plasmodium vivax infection. In addition, he had severe thrombocytopenia. These apparently serious manifestations are rare in P. vivax malaria but respond favorably to antimalarials and supportive therapy.
Keywords: Vivax malaria; acute renal failure; thrombocytopenia